A woman conflicts in a popular drama adapted from a novel - Ismail, Nor Hasimah (Universiti Malaysia Perlis, 2017)
Conflicts of soul exist because of differences in dreams, self-desires and the needs from the reality of life.This happened when someone experiences a life conflict especially when the desired thoughts and acts are not accepted by the people around him or her.This difference leads to a great mental conflict. Nowadays, novel adapted dramas are popular Adaptation is the adaptability of the situation with something new. This study will confront the conflicts experienced by female characters in the adaptation of drama from the novel, Rindu Awak 200%. The character of the woman in this drama has experienced a lot of conflicts. Accordingly, the objective of this study is to identify the image of a woman who has conflicts in the drama using text assessment. This study is hoped to become an example for the society.